Learning process and results in endoscopic saphenous vein harvesting technique - Erden, Tuncay; Gültekin, Yıldırım (Journal of Surgery and Medicine, 2021)
Background/Aim: Endoscopic saphenous vein graft harvesting (EVH) has been increasingly used in coronary bypass graft (CABG) surgery in recent years due to its cosmetic advantage and reduced morbidity. However, for the successful application of this technique, a learning process is required. In this study, we aimed to compare the results of the experience we obtained in the initial phase and later periods of the EVH technique. Methods: Forty patients who underwent elective CABG between July 2015 and April 2017 were included in this retrospective cohort study. The first 20 patients (Group 1) and the next 20 patients (Group 2), whose saphenous vein graft (SVG) was prepared with the EVH technique were compared. The length and preparation time of SVGs prepared with EVH, local findings such as hematoma, necrosis, wound infection, and healing, demographic data, comorbidity, intraoperative and postoperative data, postoperative intensive care and hospitalization times, cosmetic satisfaction and wearing compression stockings were recorded. Results: While the mean operation time was 201.4 (25.0) minutes in Group 1, it was 184.6 (17.1) minutes in Group 2 (P=0.018). There was no difference in the mean SVG lengths between the groups (P>0.05). While SVG preparation time was 75.3 (26.2) minutes in Group 1, it was 35.4 (6.0) minutes in Group 2 (P<0.001). The number of minor branch injuries in the SVG in Groups 1 and 2 were eight (40%), and two (10%), respectively, and all underwent primary repair (P<0.001). Mean length of hospital stay was similar between the groups (P=0.955). No hematoma, infection or necrosis requiring surgical intervention was observed in the extremity from which the SVG was taken. The use of compression stockings was longer in group 1 than in group 2 for the reduction or complete disappearance of edema (56.4 (23.3) vs 42.0 (19.4) days, P=0.040). No patient in any of the groups required rehospitalization due to infection at the saphenous vein incision site and incision healing problem. According to the satisfaction survey, cosmetic satisfaction was high in both groups (P=0.530). Conclusion: We think that after the completion of the learning process on twenty patients, the EVH technique can be used more widely, with much better results in terms of both patient cosmetic satisfaction and reducing morbidity.